Zastosowanie narzędzi invest do wyceny produkcji drewna jako świadczenia ekosystemów leśnych. Przykład Nadleśnictwa Złotów - Lupa, Piotr (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The subject of this article is timber production in Złotów Forest District and the evaluation of wood produced in different forest habitat types. The main goals of the study are to show the process of timber production as a forest ecosystem service, to present InVEST tools abilities in the valuation of timber production (managed timber production model). Total volume of timber produced annually in the district has been estimated at 76,3 thousand cubic meters, while the potential value of this benefit was valued at more than 21,1 million PLN. These figures show a significant variation within different forest habitat types. The studies are the author’s first step on the way to determine the total value of the forest, and should be included among activities related to the protection of forest ecosystems.
Keywords: Forest ecosystem services; Valuation; InVEST; Timber production; Forest habitat types